Limited fasciotomy in dupuytren contracture: a case report - Giri, Kadek Gede Bakta; Karna, Made Bramantya; Asmara, Anak Agung Gde Yuda; Meregawa, Putu Feryawan (International Journal of Research in Medical Sciences, 2020)
Dupuytren’s disease is a benign fibroproliferative disorder usually isolated affects the palmar fascia. The condition usually has a progressive course, from the appearance of a nodule, to the formation of a fibrous cord which pulls the finger in a flexion posture. Management from dupuytren’s disease has developed, from conservatifly, surgery, and minimal invasive. One of the conventional treatments that can be done is fasciotomy. A man, 72 years old, an Australian patient with Dupuytren’s disease that affects his 4th MCP joint. From the history it was found that the complaint had been felt since 8 years ago. Patients were do limited fasciotomy and get recovered his hand function with good result. Dupuytren’s disease is a disorder of the palmar and digital fascia that can decrease the function of patient hands. Many therapies have been developed for the treatment of this disease. From conventional treatments such as fasciotomy, to minimal invasive such as the injection of clostridium histolyticum collagenase. All of these therapies give different results and side effects. We would like to say that conventional management, especially limited fasciotomy, is still a good choice in view of the return of hand function and the minimum side effects. Limited fasciotomy gives good results, fast recovery of hand function, with minimal side effects.